Sliding contact wear and subsurface damage of CAD/CAM materials against zirconia - Wendler, M.; Kaizer, M.R.; Belli, R.; Lohbauer, U.; Zhang, Y. (Dental materials, 2020)
•Against a hard antagonist, glass-ceramics exhibit moderate wear but extensive subsurface fracture.•Resin composites show large wear craters with the absence of subsurface damage.•The polymer-infiltrated reinforced-glass material displays large wear craters and severe subsurface damage.•Under extreme occlusal loading, restoration failure can occur from excessive wear, as well as by fracture and chipping. Most previous work conducted on the wear behavior of dental materials has focused on wear rates and surface damage. There is, however, scarce information regarding the subsurface damage arising from sliding contact fatigue. The aim of this study was to elucidate the wear mechanisms and the subsurface damage generated during sliding contact fatigue in 5 contemporary CAD/CAM materials against a zirconia indenter. Forty discs (Ø12mm, 1.55mm thick) were cut out of IPS e.max CAD (e.CAD), Suprinity PC (SUP), Enamic (ENA), Vitablocs Mark II (VMII) and Lava Ultimate (LU) blocks and mirror polished. After cementation onto a dentin-like composite, off-axis mouth-motion cycling was conducted with a spherical zirconia indenter (r=3.18mm) in water (200N load, 2Hz frequency) for 5 different cycling periods (102, 103, 104, 105, 106 cycles, n=8). Analysis of the wear scars was conducted using light-microscopy, scanning-electron-microscopy and optical profilometry. Subsurface damage was assessed using sagittal and transverse sections of the samples. Fatigue wear mechanisms predominated in glassy materials (e.CAD, SUP, VMII), accompanied by extensive subsurface damage, whereas abrasive wear mechanisms were responsible for the large wear craters in the resin composite (LU) with an absolute absence of subsurface fracture. A combination of both mechanisms was observed in the polymer-infiltrated reinforced-glass (ENA), displaying large wear craters and severe subsurface damage. Well-controlled laboratory simulation can identify wear and subsurface damage susceptibility of various classes of restorative materials. Both wear and subsurface fracture are determining factors for the long-term success of restorations.